2021
DOI: 10.3389/fpubh.2021.714606
|View full text |Cite
|
Sign up to set email alerts
|

Community Drug Distributor Knowledge, Attitudes, and Motivation Surrounding Mass Drug Administration for Soil-Transmitted Helminths in India

Abstract: Background: DeWorm3 is an ongoing multi-country community-based cluster-randomized trial assessing the feasibility of interrupting transmission of soil-transmitted helminths (STH) with community-wide mass drug administration (cMDA). In Tamil Nadu, India, community drug distributors (CDDs) worked with DeWorm3 field staff to counsel community members and deliver door-to-door deworming treatment. As CDDs were likely to influence successful delivery of cMDA, we describe drivers of CDDs' knowledge, attitudes, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A positive attitude (� median composite score) towards cMDA was significantly higher among the most disadvantaged households who belonged to SC/ST. Another earlier study by our team demonstrated that a higher proportion of CDDs who belong to SC/ST households have a positive attitude towards cMDA [39]. The likelihood of perceived risk to STH infections may be higher among SC/ST households as they have poor water and sanitation facilities and less access to healthcare [40].…”
Section: Discussionmentioning
confidence: 77%
“…A positive attitude (� median composite score) towards cMDA was significantly higher among the most disadvantaged households who belonged to SC/ST. Another earlier study by our team demonstrated that a higher proportion of CDDs who belong to SC/ST households have a positive attitude towards cMDA [39]. The likelihood of perceived risk to STH infections may be higher among SC/ST households as they have poor water and sanitation facilities and less access to healthcare [40].…”
Section: Discussionmentioning
confidence: 77%
“…Participation in deworming and therefore coverage of targeted populations is influenced by several factors such as gender, socioeconomic status, population density, school attendance, local religious and cultural beliefs, awareness of helminth infections, and trust in public health campaigns [71,72]. Community engagement and sensitization activities need to be tailored to address these factors in the form of media announcements, social media, or local dissemination by trained and motivated community drug distributors (including schoolteachers) prior to national deworming campaigns [73,74]. Furthermore, sanitation and deworming alone are insufficient to address micronutrient deficiencies among children in India.…”
Section: Plos Medicinementioning
confidence: 99%